Paradigma Al-Quran Periode Makkiyah Awal Atas Realitas Zina: (Studi Tafsir Tematik Ayat-Ayat Zina) - Abdillah; Fadhil Achmad Agus Bahari (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The discussion of adultery in the Quran has received attention from many researchers, but these studies do not discuss the paradigm aspect or the way the Quran views adultery. The historical aspects behind the verses of adultery are still used limited to the object of legal verses that were revealed in the madaniyyah period. So this article is here to discuss adultery in the Quran in the Makkiyyah period and reveal the Quranic paradigm of that period on the reality of adultery. As a literature study, this research uses the primary source of the Quran, while secondary sources are obtained from books of interpretation and references related to the Quran. The method used in this research is al-tafsīr al-mauḍū'iy. The conclusion of this study shows that the way the Quran sees the reality of adultery in the Makkiyyah period focuses on strengthening aspects of faith and strengthening the economic base. In addition, the verses related to the theme have a gradual intensity, ranging from motivation to commands.